Praktik Kerjasama Pertanian Sawah Dalam Perspektif Hukum Islam Di Desa Mekarjaya Kecamatan Gantar Kabupaten Indramayu - Zainuri Zainuri; Rizal Maulana; Ali Aminullah (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Most of the Indramayu area is rice fields. The agricultural land cultivation system uses a paroan system (profit sharing system). The cooperation agreements usually made by the community are verbal, not in writing, this has become the community's habit. The aim of the research is to determine the practice of rice farming cooperation in Gantar Village, Gantar District, Indramayu Regency and to examine whether the practice of agricultural cooperation is appropriate according to Islamic law. This research uses a qualitative approach. Data collection techniques in this research are observation, interviews and documentation. Data was processed and analyzed using qualitative descriptive methods. The results of the research state that the practice of rice farming cooperation in Gantar Village, Gantar District, Indramayu Regency uses a profit sharing system. Farmers are required to become members of the Association of Farmers Supporting Food Security (P3KPI), their agreement is executed in writing, all capital is from the rice field owner, the harvest is divided in half after capital is deducted and the harvest is purchased by the rice field owner. According to Islamic law, the practice of agricultural cooperation with a profit sharing system in Mekarjaya Village, Gantar Subdistrict, Indramayu Regency is permitted, because the agreement has fulfilled the pillars and legal requirements of muzara'ah.